Infrastructure, Value Chains, and Economic Upgrades - Luo, Xubei; Xu, Xuejiao (World Bank, Washington, DC, 2018)
Infrastructure development is critical to delivering growth, reducing poverty, and addressing broader development goals. This paper surveys the literature on the linkages between infrastructure investment and economic growth, discusses the role of infrastructure in participation in global value chains and supporting economic upgrades, highlights the challenges that the least developed countries face, and provides policy recommendations. It suggests that addressing the bottlenecks in infrastructure is a necessary condition to provide a window of opportunity for an economy to develop following its comparative advantage. With the right conditions, good infrastructure can support an economy, particularly a less developed economy, to reap the benefits of participation in global value chains to upgrade the economic structure.